The effect of test-anxiety on memory among Iranian high school students. - Yousefi, Fayegh; Redzuan, Ma'rof; Mansor, Mariani; Juhari, Rumaya; Abu Talib, Mansor (Canadian Center of Science and Education, 2010)
The purpose of this paper is to determine the effect of test-anxiety on memory. The paper is based on a study, which was carried out among adolescents in Iran. The respondents of the study were 400 high school students (200 males and 200 females) in the age range of 15-19 years old. Instruments used for data collection were Test-Anxiety Inventory (25 items) and Wechsler Memory Scale –3rd Edition (WMS-III). The finding showed that test-anxiety and memory were significantly correlated, (r=-0.12, P